2013
DOI: 10.3347/kjp.2013.51.6.711
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an Allo-Transplantable Hamster Cholangiocarcinoma Cell Line and Its Application for In Vivo Screening of Anti-Cancer Drugs

Abstract: Opisthorchis viverrini (O. viverrini) is a well-known causative agent of cholangiocarcinoma (CCA) in humans. CCA is very resistant to chemotherapy and is frequently fatal. To understand the pathogenesis of CCA in humans, a rodent model was developed. However, the development of CCA in rodents is time-consuming and the xenograft-transplantation model of human CCA in immunodeficient mice is costly. Therefore, the establishment of an in vivo screening model for O. viverrini-associated CCA treatment was of interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Study characteristics are summarized in Table 1. A total of 26 studies [1035] from 2000 to 2018, focusing on various cancer types, including breast cancer [1016], liver cancer [1719], colorectal cancer [20–22], nasopharyngeal carcinoma [23, 24], lung cancer [25, 26], gastric cancer [27, 28], neuroepithelial tumor [29, 30], endometrial carcinoma [31], esophageal cancer [32], tongue cancer [33], cholangiocarcinoma [34], and sarcoma [35] were included. The studies used rats [14], hamsters [34], and mice [1013, 1533, 35] modeled via subcutaneous tumor implantation [1013, 1635] or induced tumor formation [14, 15].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study characteristics are summarized in Table 1. A total of 26 studies [1035] from 2000 to 2018, focusing on various cancer types, including breast cancer [1016], liver cancer [1719], colorectal cancer [20–22], nasopharyngeal carcinoma [23, 24], lung cancer [25, 26], gastric cancer [27, 28], neuroepithelial tumor [29, 30], endometrial carcinoma [31], esophageal cancer [32], tongue cancer [33], cholangiocarcinoma [34], and sarcoma [35] were included. The studies used rats [14], hamsters [34], and mice [1013, 1533, 35] modeled via subcutaneous tumor implantation [1013, 1635] or induced tumor formation [14, 15].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 26 studies [1035] from 2000 to 2018, focusing on various cancer types, including breast cancer [1016], liver cancer [1719], colorectal cancer [20–22], nasopharyngeal carcinoma [23, 24], lung cancer [25, 26], gastric cancer [27, 28], neuroepithelial tumor [29, 30], endometrial carcinoma [31], esophageal cancer [32], tongue cancer [33], cholangiocarcinoma [34], and sarcoma [35] were included. The studies used rats [14], hamsters [34], and mice [1013, 1533, 35] modeled via subcutaneous tumor implantation [1013, 1635] or induced tumor formation [14, 15]. BBR was administered in doses ranging between 2.5 mg/kg and 200 mg/kg body weight through intraperitoneal injection [10, 1517, 19, 21, 23, 24, 30, 33, 35] and gavage [1114, 18, 20, 22, 2529, 31, 32, 34] or from 1000 ppm to 5400 ppm in drinking water [13, 20, 25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For cell line development, fresh xenograft tissues were prepared as previously described [34]. Cells were cultured in DMEM/F12 (Wako) containing 1–10% FBS and insulin-transferrin-selenium (ITS, Gibco BRL, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have demonstrated that the therapeutic effect of BBR on cholangiocarcinoma and HCC occurs via inhibiting cancer cell proliferation and promoting cancer cell apoptosis. Puthdee et al demonstrated that the inhibitory effects of BBR on the proliferation of hamster cholangiocarcinoma cells in vitro and in vivo occurred via the induction of cell cycle arrest in the G1 phase[41].Li et al reported that BBR induces the cell cycle arrest of HCC cells in the G0/G1 phase by enhancing CDKIs p21Cip1 and p27Kip1 expression via Akt/FoxO3a/Skp2 axis regulation[42]. Saxena et al showed that BBR induces mitochondrial impairment and apoptosis of human hepatoma cells by modulating the PHLPP2-Akt-MST1 kinase signaling pathway[43].…”
mentioning
confidence: 99%